A one-pot protocol for the fluorosulfonation and Suzuki coupling of phenols and bromophenols, streamlined access to biaryls and terphenyls. Issue 25 (21st April 2020) - Li, Xinmin; Zhang, Tingting; Hu, Rui; Zhang, Hang; Ren, Changyue; Yuan, Zeli
Abstract : A one-pot protocol for the fluorosulfation and Suzuki coupling of phenols is described. Abstract : A one-pot protocol for the fluorosulfation and Suzuki coupling of phenols is described. The tandem reaction proceeds efficiently at room temperature, and various biaryls and biaryl fluorosulfates were obtained in good to excellent yields. Furthermore, biaryl fluorosulfates were utilized as versatile building blocks for the preparation of terphenyls.